PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN KONSUMEN MEMILIH PERUSAHAAN JASA - Dadi Akhmad Perdana (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
Business competition between companies in package delivery industry is currently getting tougher, because more players in this industry were arise in almost all cities in Indonesia, and also the competition with international brands that have entered the Indonesian market. However, with the increasing of online stores, the growing of business opportunities for package delivery service companies will be increase. The success of the company’s Brand Equity strategy will greatly influence with the success of a brand product in getting consumers. The better the Brand Equity, will be easier for consumers to make a decision to use the services of a service company that they will choose. In this research, the analytical method that used is descriptive analyse and uses a Likert scale in measuring the answers from respondents which aims to determine the effect of each element of brand equity i.e.: Brand awareness, Perceived quality, Brand associations and Brand loyalty to consumers’ decisions in choosing the service company they will use to send their packages